An Open-Label Non-Randomized Clinical Trial on Siddha Purgation Therapy (Bhedhi) for Pacifying Vatha disease using diagnostic tool Neikuri (International Journal of Ayurveda and Pharma Research, 2022)
Siddha system granting preventive, curative and rejuvenating healthcare. According to Siddha system three humours- Vatham, Pitham and Kapham- mediate the body’s physiological function. Derangements of trihumour lead to diseases. Vatha diseases are the most common diseases presenting in Siddha hospitals nowadays. In Siddha system the primary goal of the treatment is to restore the balance of trihumours. The first and foremost treatment for Vatha disease is Bhedhi (purgation). The quote ‘BhedhiyaalVathamthaalum’ indicates purgation therapy will reduce Vatham. For this study the purgative drug Agasthiyarkuzhambu is used. Aim and Objective: To make a validation of purgation therapy to alleviate Vathaim balance. To describe purgation therapy in alleviate Vathaim balance by giving Agasthiyarkuzhambu to outpatient and inpatient Department, Govt. Siddha Medical College, Palayamkottai. To observe the increased Vatha symptoms and Neikuri changes before and after treatment. Materials and methods: ANon randomized clinical trial was done with 40 patients, data were collected by interviewing with structured questionnaire about increased Vatha symptoms and samples of urine were collected to the analysis. The data will be analysed using SPSS. Results: Out of 40 patients, based on relief of Vatha symptoms 45% of cases reported good relief and 13% of cases reported better relief from their symptoms. In Neikuri before treatment 40% of cases had typical Vathaneikuri (fast, irregular, Aravu pol) and after treatment the Neikuri pattern changed to Pithavatham, Pitham and Kapham and only 10% of cases had Vathaneikuri. Neikuri and Vatha symptoms are better parameter for assessing alleviated Vatha imbalance in this study.